Ethical markets growing the green economy - Henderson, Hazel, 1933-; Public Broadcasting Service (U.S.); Films For The Humanities & Sciences (Firm) (Princeton, NJ. : Films for the Humanities & Sciences, 2007)
Publisher description. Featuring profiles of visionary entrepreneurs, economists, and activists, this 12-part public television series delves into hot-button ethical issues and'green business' ideas at the heart of global and local commerce. Each program investigates challenges and solutions related to the triple bottom line - standards of human dignity, environmental stewardship, and financial profit that guide socially responsible business. Building on the real-world expertise of its guests, commentators, and creator, renowned scholar Hazel Henderson, author of the engaging companion book, Ethical Markets, the series serves as a video forum for bold'green business' ideas. 12-part series, 28 minutes each
[v.1] Redefining success -- [v.2] Global corporate citizenship -- [v.3] Community investing -- [v.4] Green building and design -- [v.5] Renewable energy -- [v.6] Clean food, organic agriculture -- [v.7] Fair trade, ethical trading -- [v.8] Socially responsible investing -- [v.9] Shareholder activism -- [v.10] The love economy -- [v.11] Women-owned businesses -- [v.12] The transformation of work
End credits : c2005 by Ethical Markets Media, c2007 by Films for the Humanities & Sciences
Volume numbers assigned by cataloger in the order of the publisher's item numbers
Keywords: Sustainable development; Informal sector (Economics); Environmental responsibility; Renewable energy sources -- Economic aspects; Quality of life; Investments -- Moral and ethical aspects; Organic farming (pdal)